Extratos de folhas de annona muricata são citotóxicos e reduzem a proliferação celular em carcinoma epidermóide oral in vitro - HISS, Lorraine Stephane (2019)
Protocols for treatment of oral squamous cell carcinoma cause numerous adverse effects, which may interfere to important functions such as nutrition, phonation and respiration. Natural compounds has been studied for the treatment of cancer. Annona muricata has been used for medicinal purposes for years however its participation in the inhibition of tumorigenesis has not yet been fully elucidated. This study aimed to evaluate the effect of Annona muricata extracts on cytotoxicity and cell proliferation of SCC-4 cells of oral squamous cell carcinoma in vitro. Phytochemical screening was performed for the detection of tannins, flavonol/flavones and alkaloids at 1 mg/mL. The IC50 of extracts: chloroform (EC), ethanolic (EE) e methanolic (EM) was determinate by the Neutral Red incorporation assay for 24 h. The percentage of proliferative cells was quantified by BrdU incorporation assay at concentrations below the IC50 for 6 h. A significance of p<0.05 was considered. The quantity of tannins in EC was lower than in EE and EM (p<0.0001) and the flavonol and flavones content in EC was higher than EE and EM (p<0.001). However, the amount of tannins. However, the amout of tannins, flavonol and flavones was similar in EE and EM. No alkaloids were detected in the extracts studied by using this method. EC, EE and EM extracts were cytotoxic to SCC-4 cells, with IC50 of 6.48, 46.52 and 20.38 μg/mL, respectively. The percentage of proliferative cells was significantly lower in EC, EE and EM than the vehicle control, corresponding to an inhibition of the cell proliferation rate of 19%, 38% and, 38% respectively. These results suggest that chloroform, ethanolic and methanolic extracts of Annona muricata have a cytotoxic and antiproliferative effect on SCC-4 cells of oral squamous cell carcinoma.